2018
DOI: 10.1128/jvi.01031-17
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of Viral Mutation Rates

Abstract: Many viruses evolve rapidly. This is due, in part, to their high mutation rates. Mutation rate estimates for over 25 viruses are currently available. Here, we review the population genetics of virus mutation rates. We specifically cover the topics of mutation rate estimation, the forces that drive the evolution of mutation rates, and how the optimal mutation rate can be context-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
343
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(355 citation statements)
references
References 47 publications
(80 reference statements)
7
343
0
5
Order By: Relevance
“…Essentially, the viral mutation rate and copy number determine the variability within the host and in fine the stock of viral evolution (Duffy et al 2008;Peck and Lauring 2018;Sanjuán and Domingo-Calap 2016). Generally, viral pathogens exist in diverse populations in vivo (McCrone and Lauring 2018).…”
Section: Effects Of the Bottleneck Phenomenonmentioning
confidence: 99%
“…Essentially, the viral mutation rate and copy number determine the variability within the host and in fine the stock of viral evolution (Duffy et al 2008;Peck and Lauring 2018;Sanjuán and Domingo-Calap 2016). Generally, viral pathogens exist in diverse populations in vivo (McCrone and Lauring 2018).…”
Section: Effects Of the Bottleneck Phenomenonmentioning
confidence: 99%
“…Such high mutation rates reflect erroneous genome replication in the absence of any error correction, with only sporadic instances of RNA repair in contrast with what is seen in double-stranded DNA-based organisms (Drake 1993;Drake et al 1998;Bellacosa and Moss 2003). Across RNA viruses as a whole, estimated mutation rates fall within a range of 10 24 -10 26 mutations per site per cell replication (Sanjuán et al 2010;Sanjuán 2012;Peck and Lauring 2018), between different infected cells in the same culture or individual host (Combe et al 2015). Evolutionary rates (that is, the number of fixed substitutions per unit time) range from 10 22 to 10 25 nucleotide substitutions per site per year (Duffy et al 2008;Sanjuán 2012;Holmes et al 2016), and hence are several orders of magnitude greater than those observed in double-stranded DNA organisms (Duffy et al 2008;Sanjuán 2012).…”
Section: An Evolutionary World Shaped By Mutationmentioning
confidence: 99%
“…It is therefore no surprise that RNA viruses comprise the most important class of emerging viruses (Cleaveland et al 2001). More difficult to determine are the selective forces that have shaped the evolution of mutation rates in RNA viruses (Regoes et al 2013;Peck and Lauring 2018). One suggestion is that the genetic diversity produced by frequent mutation is in itself selectively advantageous and may directly contribute to such features as viral pathogenesis (Vignuzzi et al 2006).…”
Section: An Evolutionary World Shaped By Mutationmentioning
confidence: 99%
“…Some of the OPV's strengths (live virus, secondary transmission) are also its biggest weaknesses. Due to their error‐prone RNA‐dependent RNA polymerase, polioviruses (and picornaviruses, in general) evolve extremely rapidly at the nucleotide level, on the order of 1% per year along a chain of transmission . However, approximately 90% of these are synonymous substitutions (i.e., there is no change in the encoded amino acid), so that the same vaccines developed over 60 years ago still provide immunity to the genetically distinct wild viruses that circulate today.…”
mentioning
confidence: 99%
“…Due to their errorprone RNA-dependent RNA polymerase, polioviruses (and picornaviruses, in general) evolve extremely rapidly at the nucleotide level, on the order of 1% per year along a chain of transmission. 11 However, approximately 90% of these are synonymous substitutions (i.e., there is no change in the encoded amino acid), so that the same vaccines developed over 60 years ago still provide immunity to the genetically distinct wild viruses that circulate today. OPV strains were derived by serial passage of WPVs in cell culture and/or nonhuman primates, resulting in attenuation of replication efficiency as well as neurovirulence.…”
mentioning
confidence: 99%